2004
DOI: 10.1073/pnas.0308760101
|View full text |Cite
|
Sign up to set email alerts
|

TorsinA in the nuclear envelope

Abstract: Early-onset torsion dystonia, a CNS-based movement disorder, is usually associated with a single amino acid deletion (⌬E302͞303) in the protein torsinA. TorsinA is an AAA؉ ATPase in the endoplasmic reticulum, but what it does is unknown. Here, we use torsinA mutants with defects in ATP hydrolysis (E171Q, ATP-bound) and ATP binding (K108A, ATP-free) to probe torsinA's normal cellular function. Surprisingly, ATP-bound torsinA is recruited to the nuclear envelope (NE) of transfected cells, where it alters connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
244
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(260 citation statements)
references
References 47 publications
14
244
2
Order By: Relevance
“…Green fluorescent protein (GFP) in previously described TorA-GFP plasmids (Naismith et al, 2004) was changed to monomeric GFP (mGFP) by sitedirected mutagenesis of L221K in GFP (Snapp et al, 2003b). TorA-TagRFP was made by transferring TorA mutants excised with XhoI and EcoRI from EGFP-N1 into a RFP-N1 vector containing TagRFP (Merzlyak et al, 2007).…”
Section: Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Green fluorescent protein (GFP) in previously described TorA-GFP plasmids (Naismith et al, 2004) was changed to monomeric GFP (mGFP) by sitedirected mutagenesis of L221K in GFP (Snapp et al, 2003b). TorA-TagRFP was made by transferring TorA mutants excised with XhoI and EcoRI from EGFP-N1 into a RFP-N1 vector containing TagRFP (Merzlyak et al, 2007).…”
Section: Plasmidsmentioning
confidence: 99%
“…Although typically found throughout the ER, several things point to a function for TorA in the NE. Reducing TorA activity by gene knockout in mice or expressing a dominant negative form of the enzyme in cultured cells (Naismith et al, 2004) selectively perturbs NE structure. The NE is the favored binding site for hydrolysis deficient "substrate trap" TorA mutants (Goodchild and Dauer, 2004;Naismith et al, 2004;Kock et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within neurons, wild-type torsinA localizes to the endoplasmic reticulum (Liu et al, 2003;Naismith et al, 2004;Hewett et al, 2007), while mutant torsinA protein is found in the perinuclear space (Hewett et al, 2000;Gonzalez-Alegre and Paulson, 2004;Goodchild and Dauer, 2004). Perhaps relevant to the topic of dopaminergic dysfunction to DYT1 dystonia, associations of mutant torsinA with the vesicular monoamine transporter (VMAT2) and with alphasynuclein have been described (Sharma et al, 2001;Misbahuddin et al, 2005).…”
mentioning
confidence: 99%
“…The absence of the dystonia-associated glutamic acid (ΔE302) residue in torsinA results in the formation of aberrant membranous inclusions and redistribution of the protein to the nuclear envelope in neurons [57][58][59], thereby resulting in a net loss of native torsinA function at the ER. Other studies have implicated interactions between torsinA and cytoskeletal proteins termed nesprins that mediate connections between the nuclear envelope and cytoskeleton [60].…”
Section: Dystoniamentioning
confidence: 99%